(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
Multivariate analysis are important tools when considering all variables simultaneously. Principal component analysis using morphological variables of the West African Dwarf goats of Nigeria were carried out based on age and sex. A total of 250 goats, comprising of 143 does and 107 bucks, were used for this study. Data were collected from 10 morphological traits, including; body weight (BWT), body length (BL), height at wither (HW), rump height (RH), paunch girth (PG), heart girth (HG), ear length (EL), tail length (TL), horn length (HoL) and neck circumference (NC). Data collected were subjected to analysis procedures of SPSS (2011) statistical programme. Majority of the goats sampled were female indicating goat keepers’ preference for female than male for herd multiplication. Results of the ANOVA obtained revealed that sex had significant (P<0.05) effects on body weight, height at withers, rump height, body length, paunch girth, heart girth, ear length, horn length and neck length where female goats were significantly (P<0.05) higher than males (16.94+0.39 kg and 11.94+0.36 kg, 47.92+0.40 cm and 45.58+0.42 cm, 52.59+0.50 cm and 49.10+0.46 cm, 55.71+0.54 cm and 50.54+0.51 cm, 68.96+0.77 cm and 61.39+0.62 cm, 62.35+0.56 cm and 55.24+0.59 cm, 12.10+0.12 cm and 11.39+0.13 cm, 7.56+0.28 cm and 5.68+0.32 cm, 28.69+0.32 cm and 27.02+0.34 cm respectively) while sex had no significant (P>0.05) effect on tail length. PC1 and PC2 were extracted for all the ages of the goats, totaling to 68.798 %, 53.833 %, 47.302 % and 51.880 % respectively, of the total variances explained.